2019
DOI: 10.1080/20964129.2018.1559000
|View full text |Cite
|
Sign up to set email alerts
|

Green economic efficiency in the Yangtze River Delta: spatiotemporal evolution and influencing factors

Abstract: Based on economic-social-resource-environment perspective, which people's welfare was considered compared with the traditional perspective, using SSU and PP model, spatial analysis method, spatial econometric model to study green economy efficiency (GRE) of 26 Cities in the Yangtze River Delta from 2005 to 2015. The results show the following: Corrected GRE is markedly lower than conventional efficiency; Stage characteristics are obvious of GRE. An overall spatial pattern has emerged of lower efficiency in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The spatial lag model can show that the change in PM 2.5 in the study region is not only a local independent variable, but also a function of the changes in PM 2.5 in other spatially associated regions; in other words, changes in PM 2.5 have spatial spillover effects. The spatial error model fully reflects the effect of changes from PM 2.5 pollution in the region on random disturbances that are not included in the model, while the spatial Dubin model fully considers the effects of PM 2.5 pollution that are not reflected on the model [ 42 ]. As the standard starting point for a spatial econometric model, the spatial Dubin model is a standard framework for capturing various spatial spillover effects.…”
Section: Methodsmentioning
confidence: 99%
“…The spatial lag model can show that the change in PM 2.5 in the study region is not only a local independent variable, but also a function of the changes in PM 2.5 in other spatially associated regions; in other words, changes in PM 2.5 have spatial spillover effects. The spatial error model fully reflects the effect of changes from PM 2.5 pollution in the region on random disturbances that are not included in the model, while the spatial Dubin model fully considers the effects of PM 2.5 pollution that are not reflected on the model [ 42 ]. As the standard starting point for a spatial econometric model, the spatial Dubin model is a standard framework for capturing various spatial spillover effects.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the share of China's secondary industry is much larger than those of other countries at the same development level. The increase in the proportion of the tertiary industry has a positive impact on the improvement of regional energy efficiency (Wang et al 2019), as the development of the tertiary industry can reduce the city's excessive dependence on energy and make the city's energy consumption structure reasonable (Sun et al 2020). Thus, a shift from secondary to tertiary industry may be met with improvements in economic efficiency in China.…”
Section: The Determinants Of Environmental Performancementioning
confidence: 99%
“…The LST data were obtained from the Terra MODIS 8-days composite products (version 6) with a spatial resolution of 1000 m. The MOIDS LST data were retrieved by a generalized split-window algorithm at 10:30 h (daytime) and 22:30 h (nighttime) local solar time. Some studies showed that the retrieval errors of MODIS LST were mostly <1 K and the root mean square (RMS) was <0.5 K [28]. Because of its high quality, free availability and wide coverage, MODIS LST data have been widely used in regional thermal environment studies.…”
Section: Datamentioning
confidence: 99%